Comparison of depressive symptoms among emergency physicians and the general population in China: a cross-sectional study based on national data - Nan Jiang; Hongmei Chen; Xiaoxv Yin; Jing Wang; Yafei Wu; Mengge Tian; Jiali Zhang; Zhenyuan Chen; Jianxiong Wu; Chuanzhu Lv; Fengjie Yang; Yanhong Gong (BMC, 2024)
Abstract Background While physicians are considered to be more susceptible to developing depressive symptoms, empirical data are lacking. The study aims to compare the risk of depressive symptoms between emergency physicians and the general population in China based on national data. Methods This was a national cross-sectional study. 10 457 emergency physicians and 101 120 participants from the general population were investigated from July 2018 to August 2018 and January 2019 to February 2019, respectively. PHQ-9 was used to measure depressive symptoms, and a score ≥ 10 indicates major depression. Propensity score matching was adopted to balance the characteristics between emergency physicians and the general population. Multinomial logistic regression model was used to examine the association between occupational groups and the severity of depressive symptoms. Binary logistic regression model was performed to explore the risk factors of major depression among emergency physicians. Results The prevalence of major depression among emergency physicians was 35.7%, whereas among the general population was 13.9%. Emergency physicians had a 3.65 times higher risk of major depression than the general population. And emergency physician was significantly associated with mild (OR: 3.12, 95% CI 2.95-3.30), moderate (OR: 4.94, 95% CI 4.60-5.30), moderately severe (OR: 9.48, 95% CI 8.61-10.44), and severe depressive symptoms (OR: 14.18, 95% CI 12.47-16.13) compared with none depressive symptoms. Even after matching, the results remained consistent. Factors associated with major depression among emergency physicians included bachelor degree or above (OR: 1.22, 95% CI 1.06-1.40), worked long years (OR: 1.26, 95% CI 1.08-1.46 for 1-5 years; OR: 1.56, 95% CI 1.32-1.84 for ≥ 6 years), experienced workplace violence (OR: 2.51, 95% CI 2.16-2.94), worked more night shifts per month (OR: 1.33, 95% CI 1.16-1.51 for 6-10 times; OR: 1.83, 95% CI 1.58-2.11 for ≥ 11 times), smoked (OR: 1.64, 95% CI 1.47-1.84), and effort-reward imbalance (OR: 4.18, 95% CI 3.62-4.85). Conclusions Emergency physicians had a higher risk of depressive symptoms than the general population. There is a need for greater awareness of the mental health issues faced by emergency physicians.